Total IgE detection in paired cerebrospinal fluid and serum samples from patients with neurocysticercosis - BUENO, Ednéia Casagranda; VAZ, Adelaide José; MACHADO, Luís dos Ramos; LIVRAMENTO, José Antônio (Revista do Instituto de Medicina Tropical de São Paulo, 2000)
Neurocysticercosis (NC), the presence of Taenia solium metacestodes in tissues, is the most frequent and severe parasitic infection of the central nervous system. We investigated the presence of total IgE by an automated chemiluminescence assay in 53 paired cerebrospinal fluid (CSF) and serum samples from patients with NC (P) and in 40 CSF samples from individuals with other neurological disorders as the control group (C). Total IgE concentration ranged from 1.2 to 6.6 IU/ml (mean = 1.4 IU/ml, standard deviation-sd = 1.1 IU/ml) in 28.3% of CSF samples from the P group, a value significantly higher than for the C group (£1.0 IU/ml). The serum samples from the P group showed concentrations ranging from 1.0 to 2330.0 IU/ml (mean = 224.1 IU/ml, sd = 452.1 IU/ml), which were higher than the normal value cited by the manufacturer (<100.0 IU/ml) in 32.1% of the samples. A significant difference was observed in CSF samples from the P and C groups (p = 0.005) and in serum samples from the P group compared to the normal value (p = 0.005), with sera showing more frequent abnormal results.